Perspectives of Islamic Fiqh in the Divorce of Pregnant Women - Hidayah, Nur; Hamzah, Nur Asia; Basri, St Risnawati (Journal of Family Law and Islamic Court, 2024)
This study aims to find out the Law and Impact of divorce for pregnant women according to the perspective of Islamic jurisprudence and what will be described in this study based on two formulations of the problem, namely: 1) How the law divorces pregnant women in the perspective of Islamic jurisprudence. 2) What is the impact of divorcing a pregnant woman in the perspective of Islamic jurisprudence. In this study, the method used is the library research method, namely research by reviewing and examining data obtained from literature sources such as books, papers, articles and so on related to legal issues and the impact of divorce for pregnant women, so that precise and clear data will be obtained which then the data is compiled after going through in-depth research. The results of this study show: 1) Divorcing a wife while pregnant is permissible. The majority of scholars agree with this view, including the four imams of the madhhab namely, Imam Hanafi, Maliki, Shafi'i and Hanbali. Referring to the hadith of Ibn Umar. When he rejected his menstruating wife. Then the Prophet (peace be upon him) ordered to refer to her and then divorce when she was chaste or when pregnant and who was not allowed to divorce a pregnant woman was during menstruation, not during pregnancy. 2) The impact caused by the law, pregnant women still get a living when divorced and the iddah period is over when giving birth. As for the psychology of pregnant women losing a sense of security and comfort, discomfort is a form of guilt for leaving a partner who has been coloring her life. After divorce they tend to feel feelings such as uncertainty and loss of identity. From a social perspective, some societies consider divorce as a violation of existing moral norms, so pregnant women may experience social isolation. And from an economic point of view, pregnant women experience changes in economic status, if pregnant women depend financially on their ex-husbands.